Crystal structure determination of karibibite, an Fe3+ arsenite, using electron diffraction tomography - Colombo, Fernando (2017)
The crystal structure of karibibite, Fe3+3 (As3+O2)4(As3+2 O5)(OH), from the Urucum mine (Minas Gerais, Brazil), was solved and refined from electron diffraction tomography data [R1 = 18.8% for F > 4σ(F)] and further confirmed by synchrotron X-ray diffraction and density functional theory (DFT) calculations. The mineral is orthorhombic, space group Pnma and unit-cell parameters (synchrotron X-ray diffraction) are a = 7.2558(3), b = 27.992(1), c = 6.5243 (3) Å, V = 1325.10(8) Å3 , Z = 4. The crystal structure of karibibbite consists of bands of Fe3+O6 octahedra running along a framed by two chains of AsO3 trigonal pyramids at each side, and along c by As2O5 dimers above and below. Each band is composed of ribbons of three edge- sharing Fe3+O6 octahedra, apex-connected with other ribbons in order to form a kinked band running along a. The atoms As(2) and As(3), each showing trigonal pyramidal coordination by O, share the O(4) atom to form a dimer. In turn, dimers are connected by the O(3) atoms, defining a zig-zag chain of overall (As3+O2) n stoichiometry. Each ribbon of (Fe3+O6) octahedra is flanked on both edges by the (As3+O2) n chains. The simultaneous presence of arsenite chains and dimers is previously unknown in compounds with As3+. The lone-electron pairs (4s2 ) of the As(2) and As(3) atoms project into the interlayer located at y = 0 and y = ½, yielding probable weak interactions with the O atoms of the facing (AsO2) chain. The DFT calculations show that the Fe atoms have maximum spin polarization, consistent with the Fe3+ state.